1982
DOI: 10.1136/bmj.285.6349.1180
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-induced hypoglycaemia in an accident and emergency department: the tip of an iceberg?

Abstract: 12 Schlesinger ER. A controlled study of health education in accident prevention. Am J Dis Child 1966;3 :490-6. 13 Robertson LS, Kelley AB, O'Neill B, et al. A controlled study of the effect of television messages on safety belt use. Am J Public Health 1974;64: 1071-80. 14 Policy Services Unit. Five percent household survey. Newcastle upon Tyne: Newcastle County Council, 1979. 15 Turner S. Riverside child health project. First evaluation report. Newcastle: University of Newcastle, 1982. 16 Downham MAPS, White … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
2
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(54 citation statements)
references
References 10 publications
5
46
2
1
Order By: Relevance
“…Furthermore, 10% of all insulin treated diabetics experience at least one severe hypoglycaemic episode each year (Casparie & Elving 1985;Potter et al, 1982). Routine treatment of insulin-induced hypoglycaemia in accident and emergency rooms includes i.v.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, 10% of all insulin treated diabetics experience at least one severe hypoglycaemic episode each year (Casparie & Elving 1985;Potter et al, 1982). Routine treatment of insulin-induced hypoglycaemia in accident and emergency rooms includes i.v.…”
Section: Introductionmentioning
confidence: 99%
“…Cases treated in the hospital accident and emergency department are recognized to represent the "tip of the iceberg" (12), and the annual frequency of all emergencytreated episodes is uncertain because of incomplete ascertainment. However, this possibly has a significant resource implication from the viewpoint of ambulance use, general practitioner emergency call outs, hospital accident and emergency department attendance, and, for a small number of patients, hospital admission (13).…”
mentioning
confidence: 99%
“…Nevertheless, in patients treated with insulin, alcohol has been implicated in up to one-fifth of hospital attendances with hypoglycemia (1). Recently, in a laboratory-based study, Turner et al (2) reported that ingestion of alcohol with an evening meal increased the risk of hypoglycemia the next morning in patients with type 1 diabetes.…”
mentioning
confidence: 99%